2015
DOI: 10.1007/s00449-015-1508-2
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced butanol production in a microbial electrolysis cell by Clostridium beijerinckii IB4

Abstract: Reducing power such as NADH is an essential factor for acetone/butanol/ethanol (ABE) fermentation using Clostridium spp. The objective of this study was to increase available NADH in Clostridium beijerinckii IB4 by a microbial electrolysis cell (MEC) with an electron carrier to enhance butanol production. First of all, a MEC was performed without electron carrier to study the function of cathodic potential applying. Then, various electron carriers were tested, and neutral red (NR)-amended cultures showed an in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
37
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 37 publications
4
37
0
Order By: Relevance
“…However, the supplementation of MV gave even lower butanol production (Fig. 3 b), which may be because MV inhibits bacterial growth [ 28 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…However, the supplementation of MV gave even lower butanol production (Fig. 3 b), which may be because MV inhibits bacterial growth [ 28 ].
Fig.
…”
Section: Resultsmentioning
confidence: 99%
“…Steinbusch et al (2010) have reported an increase in more than 2 fold enhancement of ethanol production in the presence of an external source of electrical current when acetate was used as substrate for fermentation. He et al (2016), have reported 60.3% enhancement in butanol production by Clostridium spp. when neutral red was used as electron transporter.…”
Section: Discussionmentioning
confidence: 98%
“…However, electrochemically inactive bacteria can react with electrodes through the addition of an electron shuttle. In the majority of model strains, such as Escherichia coli, Actinobacillus succinogenes (Park et al, 1999) and Clostridium (He et al, 2016), bidirectional electron transfer can be achieved in the presence of electron shuttles. With neutral red, A. succinogenes can gain electrons from a cathode and use these for intracellular metabolism (Park et al, 1999).…”
Section: Extracellular Electron Transfer In Microbial Electrochemical Systemsmentioning
confidence: 99%